The relationship between self-efficacy, health literacy, and quality of life in patients with chronic diseases: a cross-sectional study in China - Gao, Ying’e; Zheng, Yujia; He, Yuanyuan; Lin, Jingjing; Liu, Fangyi; Fu, Jie; Lin, Rongjin (Frontiers in Public Health, 2024)
Background Self-efficacy and health literacy are closely related to the quality of life in patients with chronic diseases; however, it remains unclear whether their combined effects on the quality of life (QoL) in these patients operate through mediation, interaction, or a combination of both. Methods The research occurred in China between July 10 and September 15, 2021. A multi-stage random sampling technique was utilized to gather information on self-efficacy, health literacy, and QoL among individuals with chronic diseases. Linear regression models investigated the relationships between these patients’ self-efficacy, health literacy, and QoL. Additionally, the four-way decomposition method was used to decompose the overall effects of self-efficacy and health literacy on the QoL in patients with chronic diseases. Results Significant correlations were found between self-efficacy, health literacy, and QoL among individuals with chronic diseases (all p < 0.05). In the four-way decomposition results, the results of the European Quality of Life Five Dimension Five Level (EQ-5D-5L) displayed the interaction effects mediated by self-efficacy, and the reference interaction effects were not significant, with small effect sizes observed. The influence of health literacy levels on the QoL in these patients was primarily attributed to the controlled direct effect (CDE), accounting for approximately 86.12% [excess relative risk = 0.00415; 95% CI: 0.00326, 0.00504; p < 0.0001]. The proportion solely attributable to the pure indirect effect (PIE) of self-efficacy was 14.5% [excess relative risk = 0.0007; 95% CI: 0.00031, 0.00109; p < 0.0001]. In the EQ visual analog scale (EQ-VAS) results, the proportion of the controlled direct effect was 84.9% [excess relative risk = 0.62443; 95% CI: 0.52269, 0.72618; p < 0.0001], while the proportion solely attributable to the pure indirect effect of mediation was 14.8% [excess relative risk = 0.10876; 95% CI: 0.06409, 0.15344; p < 0.0001]. Conclusion Self-efficacy and health literacy primarily influence QoL in patients with chronic diseases through controlled and pure indirect effects. Enhancing patients’ health literacy and self-efficacy can contribute to improving their QoL.